Analysis of the ex vivo and in vivo antiretroviral activity of gemcitabine. - Christine L Clouser; Colleen M Holtz; Mary Mullett; Duane L Crankshaw; Jacquie E Briggs; Jay Chauhan; Ilze Matise VanHoutan; Steven E Patterson; Louis M Mansky (PLoS ONE, 2011)
Replication of retroviral and host genomes requires ribonucleotide reductase to convert rNTPs to dNTPs, which are then used as substrates for DNA synthesis. Inhibition of ribonucleotide reductase by hydroxyurea (HU) has been previously used to treat cancers as well as HIV. However, the use of HU as an antiretroviral is limited by its associated toxicities such as myelosuppression and hepatotoxicity. In this study, we examined the ribonucleotide reductase inhibitor, gemcitabine, both in cell culture and in C57Bl/6 mice infected with LP-BM5 murine leukemia virus (LP-BM5 MuLV, a murine AIDS model). Gemcitabine decreased infectivity of MuLV in cell culture with an EC50 in the low nanomolar range with no detectable cytotoxicity. Similarly, gemcitabine significantly decreased disease progression in mice infected with LP-BM5. Specifically, gemcitabine treatment decreased spleen size, plasma IgM, and provirus levels compared to LP-BM5 MuLV infected, untreated mice. Gemcitabine efficacy was observed at doses as low as 1 mg/kg/day in the absence of toxicity. Higher doses of gemcitabine (3 mg/kg/day and higher) were associated with toxicity as determined by a loss in body mass. In summary, our findings demonstrate that gemcitabine has antiretroviral activity ex vivo and in vivo in the LP-BM5 MuLV model. These observations together with a recent ex vivo study with HIV-1, suggest that gemcitabine has broad antiretroviral activity and could be particularly useful in vivo when used in combination drug therapy.